Analysis of Students’ Learning Motivation in Learning Buffer Solutions Using Instructional Videos - Miessya Wardani; Mutia Shafira (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2026)
Buffer solutions are challenging for students, often affecting their motivation. This study analyzed learning motivation in the use of instructional videos on buffer solutions. The study used a quantitative descriptive approach with 35 twelfth-grade students in Parung and collected data via a closed-ended questionnaire examining video presentation and learning motivation. Results showed 60% of students had high motivation, and 40% had very high motivation. Nevertheless, teacher guidance remains crucial to support diverse learning styles.